H2S PROPERTIES AND INITIAL RESPONSE STRATEGY TO SAFE WORKING AT OFFSHORE - subiyanto subiyanto; Ariana Oktavia (UNIMAR AMNI Semarang, 2020)
Hydrogen sulphideor H2S is a naturally occurring gas found in a variety of geological formation. It is also formed by the natural decomposition of organic material in the absence of oxygen. It is encountered in a variety of industrial processes, including sewage and waste water treatment facilities and the production also refining of petroleum, pulp and paper, metals, acid gas, stink dump,vessels, etc.H2S gas is colorless, heavier than air and extremely toxic in small concentrations, it has a rotten egg smell, causes eye and throat irritation. H2S can deaden your sense of smell; at higher concentrations can causes death. For these reason training in how to protect you is crucial in any industry and places where H2S might be encountered. You will know more about the toxic effect and dangers of H2S, but first take a look at the following fatality incidents, which occurred in the petroleum industry. All of this incident could have been prevented.The data were collected by using study of literature and observation.the suggestionto overcome the problem are cautions when dealing with any confined space and if near oil and gas facilities check wind direction.